Nature inspired materials: Emerging trends and future prospects - Goel, Saurav; Hawi, Sara; Goel, Gaurav (Cranfield University, 2020)
Nature inspired materials images
Keywords: 'Nature Inspired Algorithm (NIA)'; 'Biomechanical Engineering'; 'Biomedical Engineering not elsewhere classified'; 'Manufacturing Processes and Technologies (excl. Textiles)'; 'Mechanical Engineering'